Fiscal Deficits and Current Account Deficits - Kumhof, Michael (IMF Working Papers; Working Paper ;, 2009)
The effectiveness of recent fiscal stimulus packages significantly depends on the assumption of non-Ricardian savings behavior. We show that, under the same assumption, fiscal deficits can have worrisome implications if they turn out to be permanent. First, if they occur in large countries they significantly raise the world real interest rate. Second, they cause a short run current account deterioration equal to around 50 percent of the fiscal deficit deterioration. Third, the longer run current account deterioration equals almost 75 percent for a large economy such as the United States, and almost 100 percent for a small open economy.